Genomic Insecurity: Kebocoran Data 23andMe dan Transformasi Biosecurity terhadap Identitas Genetik dalam Perspektif Human Security - Adinda Gladys Hartisya; Imam Fadhil Nugraha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This paper analyzes the genetic data breach experienced by the biotechnology company 23andMe in 2023 and its impact on individual security, focusing on the transformation of genetic data into an instrument of power within the framework of non-traditional security threats. Using a descriptive analytical method based on a literature review, this paper explores three main dimensions; the credential stuffing attack mechanism that exploited the DNA Relatives feature, thereby exposing millions of user accounts globally; the operationalization of corporate biopower through the Direct-to-Consumer model that positions 23andMe as a non-state biological administrator, and the relational and hereditary nature of genetic data that extends the threat to family networks and future generations. These are analyzed through the integration of Michel Foucault’s biopolitical theory and human security, with the dimension of health security serving as the primary analytical framework. Therefore, this paper demonstrates that the 23andMe data breach is not merely a technical cyber failure, but rather a manifestation of the shift in the logic of bio-surveillance from state authorities to the realm of commercial corporations, creating permanent, systemic, and unequal vulnerabilities.